Governance of institutional complexity in megaproject organizations. Issue 3 (April 2019) - Qiu, Yumin; Chen, Hongquan; Sheng, Zhaohan; Cheng, Shuping
Abstract: A significant research gap exists in our understanding of how to govern institutional complexity in megaproject organizations. In this paper, we conduct a case study of the Hong Kong-Zhuhai-Macao Bridge project in order to elaborate on whence institutional complexity emerges and how institutional complexity affects project outcomes and shapes actors' behaviors. We find that institutional complexity stems from both external (macro-level) environments and internal actors (micro-level environments), and consists of regulatory, political, and social complexity and cultural, evolutionary, and relational complexity, respectively. In addition, we find that institutional complexity from the macro environments will result in constraint conflicts in megaproject organizations, whereas the different practices and identities of the project's various micro-actors will create organizational conflicts. We also find that actors within the megaproject organizations choose different responses when faced with different types of institutional complexity. Our approach offers conceptual refinements and a new sensitizing framework for guiding studies of how, in practice, to govern institutional complexity of megaproject organizations. Highlights: Institutional complexity stems from macro-level environments and micro-level actors. Different types of institutional complexity exert different impacts on megaproject organizations. Actors within megaproject organizations respond differently to different types of institutional conflicts. This study offers four governance mechanisms to effectively resolve institutional complexity.